Extensive necrotizing fasciitis of scrotum and abdominal wall: Report of two cases and a review of the literature - Meng, Zhe; Wang, Yanchen; Chao, Jun; Ji, Yongjian; Sun, Yaofei; Zhu, Jiang; Gao, Tongbin; Chen, Si; Wang, Shenyang (Frontiers in Surgery, 2022)
The incidence rate of necrotizing fasciitis(NF) is low, but it has a high mortality rate. At present, it lacks experience in clinical treatment in municipal and county-level hospitals, insufficient awareness of disease risk, lack of experience in disease surgical intervention, and lack of a set of mature treatment norms and standards. Most patients have no time to transfer to a higher hospital for treatment. In January and April 2022, two cases of large-scale necrotizing fasciitis of the scrotum and abdominal wall were treated in the Department of Urology of Weifang people's Hospital respectively and were clinically cured after active surgical debridement combined with broad-spectrum antibiotics. Through the retrospective analysis of the diagnosis and treatment of two cases of necrotizing fasciitis, this paper analyzes and summarizes the scope of surgical debridement of NF, postoperative dressing changing skills, timing of multiple debridements, application and timing of vacuum sealing drainage(VSD), and the combined use of antibiotics. To provide experience for clinical diagnosis and treatment of necrotizing fasciitis.